Influence of wilderness experience on the adoption of environmentally responsible behaviour - De Wet, Benita (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2007.